1997
DOI: 10.1109/36.628795
|View full text |Cite
|
Sign up to set email alerts
|

The MODIS 2.1-μm channel-correlation with visible reflectance for use in remote sensing of aerosol

Abstract: For this reflectivity range the dust radiative effect at 2.2 m is small, and the surface reflectance in the blue and red channels can be retrieved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
417
3
10

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 764 publications
(446 citation statements)
references
References 33 publications
16
417
3
10
Order By: Relevance
“…The ENVI™ FLAASH (Fast Line of sight Atmospheric Analysis of Spectral Hypercubes) atmospheric correction module was applied to Landsat and HJ-1 images to derive the sea surface reflectance (R, unitless). FLAASH includes a method for aerosol estimation based on the dark pixel reflectance ratio method (Kaufman, Wald, Remer, Gao, Li, & Flynn, 1997), which has been successfully used in the atmospheric correction of multi-band or hyperspectral images over waters (e.g., Kutser, Pierson, Kallio, Reinart, & Sobek, 2004;Kutser, 2012;Tian, Lu, Chen, Yu, Xiao, Qiu, & Zhao, 2010;Moses, Gitelson, Perk, Gurlin, Rundquist, Leavitt, Barrow, & Brakhage, 2012;Zeng, Zhao, Tian, & Chen, 2013). The requirement of absolute accuracy of atmospheric correction in this study, however, is not critical because it is the relative height of the near-infrared band that is used for detecting and quantifying macroalgae.…”
Section: Satellite Datamentioning
confidence: 99%
“…The ENVI™ FLAASH (Fast Line of sight Atmospheric Analysis of Spectral Hypercubes) atmospheric correction module was applied to Landsat and HJ-1 images to derive the sea surface reflectance (R, unitless). FLAASH includes a method for aerosol estimation based on the dark pixel reflectance ratio method (Kaufman, Wald, Remer, Gao, Li, & Flynn, 1997), which has been successfully used in the atmospheric correction of multi-band or hyperspectral images over waters (e.g., Kutser, Pierson, Kallio, Reinart, & Sobek, 2004;Kutser, 2012;Tian, Lu, Chen, Yu, Xiao, Qiu, & Zhao, 2010;Moses, Gitelson, Perk, Gurlin, Rundquist, Leavitt, Barrow, & Brakhage, 2012;Zeng, Zhao, Tian, & Chen, 2013). The requirement of absolute accuracy of atmospheric correction in this study, however, is not critical because it is the relative height of the near-infrared band that is used for detecting and quantifying macroalgae.…”
Section: Satellite Datamentioning
confidence: 99%
“…Based on the assumptions about the properties of the Earth's surface and the aerosol type expected over these surfaces, the MODIS Atmosphere team developed three algorithms for processing MODIS observations (Levy et al, 2013). Regions which appear visually dark from space, referred to as dark target (DT), include the algorithm assumptions for vegetated land surfaces (Kaufman et al, 1997a, b) and for remote ocean regions (Tanré et al, 1997). The third algorithm, called the deep blue (DB) algorithm, includes assumptions for surfaces which are visually bright from space and uses near-UV wavelengths (DB band near 410 nm).…”
Section: Modis Satellite Instrumentsmentioning
confidence: 99%
“…This comparative analysis does not aim to be a validation study of the MODIS sensor since many works during the long history of the MODIS sensor on the Terra and Aqua platforms have sought to improve its features (these include Kaufman et al, 1997a, b;Tanré et al, 1997;Remer et al, 2002Remer et al, , 2005Remer et al, , 2006Hsu, et al, 2004Hsu, et al, , 2006Hsu, et al, , 2013Levy et al, 2007Levy et al, , 2009Levy et al, , 2010Levy et al, , 2013Levy et al, , 2015Sayer et al, 2013Sayer et al, , 2014 https://darktarget.gsfc.nasa.gov/atbd/overview, last access: 9 April 2018). However, compared to other areas of the world, no studies have been reported in the Caribbean region and in Cuba in particular (Papadimas et al, 2009;Mishchenko et al, 2010;Kahn et al, 2011;Bennouna et al, 2011Bennouna et al, , 2013Witte et al, 2011;Gkikas et al, 2013Gkikas et al, , 2016Levy et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Based on the guidelines given in the FLAASH User's Guide (2008), the atmospheric model, which is based on the geographic location and the season of the year at the time of image acquisition, was chosen as 'Mid-Latitude Summer' for the 02 Jul, 14 Jul, 26 Sep, and 25 Oct images, and 'Sub-Arctic Summer' for the 19 Nov image. The aerosol retrieval method implemented in FLAASH is the approach suggested by Kaufman et al (1997), which involves selecting dark surface pixels in the image based on the at-sensor radiances at channels near 660 nm and 2100 nm. Since AISA does not have a spectral channel near 2100 nm, it was not possible to automatically retrieve aerosol properties from the image data using FLAASH.…”
Section: Flaash Atmospheric Correctionmentioning
confidence: 99%